Gaya Komunikasi Pemasaran di Pemerintah: Promotion Mix Destinasi Tujuan Wisata Kabupaten Raja Ampat - Rafa'al, Mubaddilah (Faculty of Communications Science, Dr. Soetomo University, 2017)
This study focuses on the description of Promotion marketing mix used by the Department of Culture and Tourism Raja Ampat. This research is interesting because it is a means of marketing communications for the company in order to inform the products to be introduced to tourists, persuade and improve the consumer directly or indirectly about the services they offer. This study aimed to describe the promotion mix used the Department of Culture and Tourism Raja Ampat. In order to know that the Department of Culture and Tourism Raja Ampat has managed to reach the desired rating. The method used in this study using in-depth interview, the quotation in question and answer activities between researchers and resource speakers. With respect to achieving success in the marketing process, the Department of Culture and Tourism Raja Ampat using promotion mix include advertising, sales promotion, public relations, personal selling, direct marketing, and internet marketing.Â Keywords: Promotion mix, tourists, Department of Culture and Tourism Raja AmpatÂ